Formally integrating Generative AI into secondary education: Application of ChatGPT in EFL writing instruction - Leisi Pei, Morris Siu-Yung Jong, Biyun Huang, Wai-Chung Pang and Junjie Shang (Educational Technology & Society, 2025)
ChatGPT, which rides on generative artificial intelligence (AI) technology, has garnered exponential attention worldwide since its release in 2022. While there is an increasing number of studies probing into the potential benefits and challenges of ChatGPT in education, most of them confine the focus to informal learning and higher education. The formal adoption of ChatGPT in authentic classroom settings, especially in K-12 contexts, remains underexplored. In view of this gap, we conducted a quasi-experiment to study the effects of integrating ChatGPT into a compulsory Grade-10 English as a foreign language (EFL) writing course in a Hong Kong secondary school. The participants (99 Grade-10 students) were divided into treatment or control groups; the former and latter respectively used ChatGPT and conventional media as the tool for EFL writing instruction. The analysis of the participants’ EFL writing performance at the end of the experiment shows that the treatment group outperformed the control group. Further, there was a significant interaction effect between the assigned group of participants and their baseline level of EFL proficiency. Compared to the high-achieving participants, low-achieving ones tended to benefit more from ChatGPT-supported EFL writing instruction in the experiment. These findings together suggest that ChatGPT has the potential to be applied in formal EFL writing instruction in K-12 classroom settings.